Una mirada ética al envejecimiento desde diferentes culturas y sociedades (Paraninfo Digital, 2024)
.
Keywords: s:5:"Ética"; s:14:"Envejecimiento"; s:7:"Cultura"; s:8:"Sociedad"; s:21:"Servicios de atención"; s:8:"Benestar"; s:15:"Adultos mayores"; s:29:"Atención médica de vanguardia"; s:7:"Avances"; s:7:"Calidad"